Case Report: D-bifunctional protein deficiency caused by novel compound heterozygote HSD17B4 variants in a neonate in China - Liu, Hui; Liu, Gaojie; Gao, Lianjun; Wang, Hui; Wang, Yizhong; Ding, Hongfang (Frontiers in Genetics, 2025)
BackgroundD-bifunctional protein deficiency (D-BPD) is a rare fatal autosomal recessive peroxisomal disorder caused by biallelic pathogenic mutations in the hydroxysteroid 17-beta dehydrogenase 4 (HSD17B4) gene; it is characterized by hypotonia, seizures, and facial dysmorphisms during the neonatal period.Case presentationIn this report, we describe a female neonate from China who was diagnosed with D-BPD. The patient presented with neonatal asphyxia, hypotonia, weak reflexes, and feeding difficulty after birth. Seizures occurred on the fifth day of life and were initially treated with phenobarbital. However, the seizures reoccurred and became more difficult to control because of their increased frequency, duration, and anticonvulsive drug resistance. Whole-genome sequencing (WGS) revealed novel compound heterozygous mutations c.1145G>A(p.Gly382Asp)/c.1193C>G(p.Ser398*) in exon 13 of the HSD17B4 gene, which was confirmed by parental Sanger sequencing. Neither variant has been reported previously. Very-long-chain fatty acid (VLCFA) testing revealed markedly elevated levels of hexacosanoic acid (C26:0), tetracosanoic acid/docosanoic acid (C24:0/C22:0), and C26:0/C22:0. The patient was managed with formula nasogastric feeding and antiepileptic therapy. At 7 months of age, she demonstrated severe psychomotor retardation, inability to grasp and manipulate objects, no language development, hearing loss, and poor visual response.ConclusionWe described the incidence of D-BPD in a Chinese neonate caused by novel biallelic pathogenic variants in HSD17B4, which expands its mutational spectrum.